A review of immunotargeted therapy for Philadelphia chromosome positive acute lymphoblastic leukaemia: making progress in chemotherapy-free regimens - Zhen-Yu Xiong; Yao-Jia Shen; Shi-Zhong Zhang; Hong-Hu Zhu (Hematology, 2024)
Philadelphia chromosome-positive acute lymphoblastic leukemia (PH + ALL) is the most common cytogenetic abnormality of B-ALL in adults and is associated with poor prognosis. Previously, the only curative treatment option in PH + ALL was allogeneic hematopoietic stem cell transplantation (Allo-HSCT). Since 2000, targeted therapy combined with chemotherapy, represented by the tyrosine kinase inhibitor Imatinib, has become the first-line treatment for PH + ALL. Currently, the remission rate and survival rate of Imatinib are superior to those of simple chemotherapy, and it can also improve the efficacy of transplantation. More recently, some innovative immune-targeted therapy greatly improved the prognosis of PH + ALL, such as Blinatumomab and Inotuzumab Ozogamicin. For patients with ABL1 mutations and those who have relapsed or are refractory to other treatments, targeted oral small molecule drugs, monoclonal antibodies, Bispecific T cell Engagers (BiTE), and chimeric antigen receptor (CAR) T cells immunotherapy are emerging as potential treatment options. These new therapeutic interventions are changing the treatment landscape for PH + ALL. In summary, this review discusses the current advancements in targeted therapeutic agents shift in the treatment strategy of PH + ALL towards using more tolerable chemotherapy-free induction and consolidation regimens confers better disease outcomes and might obviate the need for HSCT.